The Law of partnerships and private corporations - De Leon, Hector S.; De Leon, Jr., Hector M. (Manila, Philippines : Rex Book Store, 2013)
This modest work which is actually the eleventh edition is primarily intended for the use of commerce students. However, law students and even numbers of the Bench and the Bar will find it a useful reference.
Part 1: Partnership -- 1. General provision -- 2.Obligation of the partners -- 3. Dissolution and winding up -- 4.Limited partnership -- Part 2: Private corporation code of the Philippines -- Title 1: General provisions -- Title 2: Incorporation and organization of private corporations -- Title 3: Board of directors/ trustees/ officers -- Title 4. Powers of corporations --Title 5: By-laws -- Title 6: Meetings -- Title 7: Stocks and stockholders -- Title 8: Corporate books and records -- Title 9: Merger and consolidation -- Title 10. Appraisal right -- Title 11: Non-stock corporations -- Title 12: Close corporations -- Title 13: Special corporations -- Title 14: Dissolution -- Title 15: Foreign corporations -- Title 16: Miscellaneous provisions
Keywords: COMMERCIAL LAW